1988
DOI: 10.5144/0256-4947.1988.425
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening for Hip Instability: Five Years' Experience

Abstract: All newborn infants delivered at King Fahd Hospital of the University in Al-Khobar between June 1982 and May 1987 were subjected to routine physical examinations, including the Ortolani and Barlow maneuvers for detection of hip instability. A total of 12,733 neonates were screened, and a positive test was found in 62 (0.49%). Infants with a positive test were placed in a von Rosen splint for 6 to 8 weeks. Five "missed" cases were diagnosed later, all of whom were born during the first year of the study. Male-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 12 publications
2
22
1
Order By: Relevance
“…The female predominance is in keeping with other reports from the Middle East and the West [3,10]. The proportion of bilateral instability and left laterality are similar to Western figures [12] and at variance with Mufti's [13] data from Riyadh as shown in Table 5.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The female predominance is in keeping with other reports from the Middle East and the West [3,10]. The proportion of bilateral instability and left laterality are similar to Western figures [12] and at variance with Mufti's [13] data from Riyadh as shown in Table 5.…”
Section: Discussionsupporting
confidence: 76%
“…This is comparable to the incidence found in some communities such as the Lapps, American Indians, and the Japanese in the early sixties [2,7]. Al-Umranet al [3] reported a lower incidence (0.49%) with congenital hip instability in a hospital born cohort over a five-year period from the Eastern Province of Saudi Arabia. This suggests a true regional variation in the incidence of hip instability within the country.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…No case of femoral head necrosis was observed using the von Rosen splint. 1 It is suggested that three to five babies may be splinted unnecessarily for every one benefiting from the procedure. 2,15 Yet considering: a) the serious long-term morbidity in overlooked cases; b) the poor results of late intervention; and c) the lack of complications and minor inconvenience of the splintage, it may be argued that the screening and management program should continue.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences in the Eastern Province of Saudi Arabia are evidence in point. 1,2 The benefits of screening are substantial and very few cases are overlooked at birth if a sustained screening program is in operation. 3 Routine screening of all neonates at the King Fahd Hospital of the University (KFHU) began in 1982G, with the necessary cooperation between the Departments of Pediatrics and Orthopedics in the diagnosis and management of neonates with unstable hips.…”
mentioning
confidence: 99%